TÃO LONGE DO INFERNO, TÃO PERTO DO CÉU: AMEDRONTAR PARA CONVERTER - Fleck, Eliane Cristina D. (História: Questões & Debates, 2003)
A análise do impacto das concepções cristãs-ocidentais acerca da doença e da morte na sensibilidade indígena guarani e sua tradução, em termos de representações e práticas sociais, nas reduções jesuítico-guaranis, circunscritas à Província Jesuítica do Paraguai, no século XVII, é o tema deste trabalho. Para uma compreensão das reduções jesuítico-guaranis na perspectiva de uma história da sensibilidade, procedeu-se a uma releitura das Cartas Ânuas da Província Jesuítica do Paraguai, referentes ao período de 1609 a 1675. O discurso jesuítico, especialmente através de suas falhas, permitiu reconhecer as reduções como espaço de reinvenção de significados, no qual se constrói uma sensibilidade religiosa própria, resultante da acomodação criativa da espiritualidade guarani e da devoção e piedade tridentinas. So far the hell, so near the heaven: scare to convert Abstract The analysis of the impact of Western Christian conceptions of illness and death in the Guarani indigenous sensibility and their translation into the Guaranis representations and social practices, in the Jesuit mission settlements (reducciones) of the Guarani, circumscribed to the Jesuit Province of Paraguay, constitutes the theme of the present research. An in-depth reading of the Cartas Ânuas of the Jesuit Province of Paraguay, concerning the period from 1609 to 1675, was carried out to come to a deeper understanding of Jesuit-Guarani mission settlements within the framework of a history of sensibility. The Jesuit discourse, mostly through its gaps, allowed for the acknowledgement of the Mission Settlements as a space for the reinvention of meanings, in which it is possible to construct a unique religious sensibility that results from the creative accommodation of Guarani spirituality and of Tridentine devotion and piety.